A NOTE ON â€œMULTIATTRIBUTE DECISION MAKING BASED ON INTERVAL-VALUED INTUITIONISTIC FUZZY VALUES AND LINEAR PROGRAMMING METHODOLOGYâ€ - KAUR*, ARSHDEEP (International Journal of Mathematical Archive, 2018)
Chen and Huang (Inf. Sci. 381 (2017) 341-351) proposed a linear programming method for solving such MADM (multiattribute decision making) problems in which the weights of attributes and the evaluating values of the attributes of the alternatives are represented by interval-valued intuitionistic fuzzy values. After a deep study of this method, it is noticed that there exist several same types of MADM problems which cannot be solved with Chen and Huang method. To solve these type of MADM problems is a challenging research problem. Therefore, the aim of this note is to make the researchers aware of this open challenging research problem.